Differences in Report of Post-COVID Conditions Among Adults Tested for SARS-CoV-2 by Race and Ethnicity: 2022 Porter Novelli SummerStyles Survey, U.S. - Leora R. Feldstein, PhD, MSc; Deja Edwards, MPH; Jennifer R. Cope, MD, MPH; Melissa Briggs Hagen, MD, MPH; Sharon Saydah, PhD, MHS (Elsevier, 2024)
Introduction: Since March 2020, Hispanic and Black/African American persons have made up a disproportionate number of COVID-19 cases, hospitalizations, and deaths. However, little is known about whether the prevalence of postacute sequelae or post-COVID conditions differs by race/ethnicity. Methods: This study used cross-sectional survey data collected by Porter Novelli Public Services to determine the prevalence of ≥1 ongoing symptom lasting ≥4 weeks by SARS-CoV-2 test status and racial/ethnic groups among 2,890 adults in the U.S. Results: Overall, 57% (95% CI=54%, 60%) of respondents with positive SARS-CoV-2 tests reported ≥1 ongoing symptom, compared with 22% (95% CI=20%, 24%) of respondents who tested negative. Among those with positive SARS-CoV-2 tests, Hispanic respondents had higher AORs of experiencing ≥1 ongoing symptom (AOR=1.79, 95% CI=1.27, 2.53) than non-Hispanic White respondents. In addition, Hispanic respondents had significantly higher ORs of experiencing 2 or more ongoing symptoms (AOR=2.03, 95% CI=1.45, 2.86), respiratory/cardiac symptoms (AOR=1.47, 95% CI=1.03, 2.07), neurologic symptoms (AOR=1.77, 95% CI=1.26, 2.48), and other symptoms (AOR=1.53, 95% CI=1.09, 2.14) than non-Hispanic White respondents. Non-Hispanic other respondents who reported at least 1 positive SARS-CoV-2 test had significantly higher ORs of experiencing gastrointestinal symptoms (AOR=4.06, 95% CI=1.78, 8.89) than non-Hispanic White respondents. Conclusions: These results highlight potential disparities in ongoing symptoms, even after accounting for demographic differences, and reinforce the need for culturally appropriate and targeted strategies to increase access to health care and reduce SARS-CoV-2 infections.